Visual loop-mediated isothermal amplification (LAMP) assay for specific detection of groundnut ringspot and tomato spotted wilt orthotospoviruses - De Breuil, Soledad (2026)
Groundnut ringspot virus (GRSV; Orthotospovirus arachianuli) and tomato spotted wilt virus (TSWV; Orthotospovirus tomatomaculae) pose a significant threat to agricultural crops worldwide. Managing the diseases they cause is particularly challenging due to their broad host range and transmission by thrips vectors. Early and accurate detection is crucial, especially given the limitations of conventional serological and molecular diagnostic methods. This study introduces reverse transcription loop-mediated isothermal amplification (RT-LAMP) as a reliable alternative for detecting and identifying GRSV and TSWV in tomato, pepper, and peanut plants. Primer sets were designed to specifically amplify fragments of the nucleoprotein gene of each virus. RT-LAMP yielded negative results in healthy plants and showed no cross-reactivity with closely related orthotospoviruses or viruses from other genera. RT-LAMP detected viral RNA in total RNA samples down to 5 pg/µl, showing greater sensitivity than RT-PCR. Field testing on symptomatic plants further validated the effectiveness of this technique. This study highlights RT-LAMP as a rapid, species-specific, and highly sensitive tool for the early detection of GRSV and TSWV in economically important crops, offering a valuable approach to improving disease management. Notably, this work is the first to report the development of an RT-LAMP assay for the specific detection of GRSV.